Efficacy of fungicides in controlling fusarium wilt of gladiolus - Yasmin, L; Ali, MA; Khan, FN (Bangladesh Journal of Agricultural Research, 2018)
The efficacy of fungicides in controlling Fusarium wilt of gladiolus was studied at Horticulture Research Centre (HRC), Bangladesh Agricultural Research Institute (BARI), Gazipur during 2010-2012 following RCB design with four replications. Six fungicides such as Bavistin (0.1%), Provax (0.2%), Mancozeb (0.2%), Rovral (0.2%), Chlorax (10%) and Cupravit (0.7%) were evaluated against the Fusarium wilt disease of gladiolus (Fusarium oxysporum f. sp. gladioli) under naturally infested field condition. Bavistin was very effective in reducing the disease incidence and thereby resulting maximum corm germination (99.98%), spike length (73.90 cm), rachis length (43.70 cm), florets spike-1 (12.63), flower sticks plot-1 (38.75) and corm plot-1 (60.23) and cormel yield ha-1 (2.51 t) of gladiolus. Provax and Cupravit were also effective in inhibiting the disease incidence as well as better spike length, rachis length, florets spike-1, no of flower sticks, corm and cormel yield. Bangladesh J. Agril. Res. 42(4): 599-607, December 2017